Arthur White Collection, Correspondence from Time Medicine to London division, July 22, 2016. - Unknown, Unknown (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, December 7, 2016., 1978)
Correspondence from Time Medicine to London division in reference to the impending birth of the first "test-tube baby" by Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe (Gynecologist) and Robert Edwards (Physiologist).
Digitized from original print, Valdosta State University Archives and Special Collections, December 7, 2016.
Keywords: Test tube baby; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; Time Magazine; Time Magazine Medicine; Time Medicine; Arthur White; Lesley Brown; John Brown; Lousie Joy Brown; Patrick Steptoe; Professor Sir Robert Edwards; Robert Edwards; Oldham General Hospital; Oldham, England; London, England; England; Great Britain; 1970s; 1978